2022
DOI: 10.3390/ijms23063037
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Effects on Neuronal Energy Metabolism Correlate with Activity States While Mitochondrial Function Remains Intact

Abstract: During general anesthesia, alterations in neuronal metabolism may induce neurotoxicity and/or neuroprotection depending on the dose and type of the applied anesthetic. In this study, we investigate the effects of clinically relevant concentrations of sevoflurane (2% and 4%, i.e., 1 and 2 MAC) on different activity states in hippocampal slices of young Wistar rats. We combine electrophysiological recordings, partial tissue oxygen (ptiO2) measurements, and flavin adenine dinucleotide (FAD) imaging with computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Compared to our other in vitro studies, the SD-related increase in CMRO 2 (2.7-fold) was significantly higher than during other energy-demanding types of network activity, such as gamma oscillations or seizure-like events, which induced a 1.3-fold and 1.4-fold increase in CMRO 2 , respectively. 30,54 This underlines the great metabolic demand induced by SD.…”
Section: Cmro 2 Increases 27-fold During Sdmentioning
confidence: 91%
See 2 more Smart Citations
“…Compared to our other in vitro studies, the SD-related increase in CMRO 2 (2.7-fold) was significantly higher than during other energy-demanding types of network activity, such as gamma oscillations or seizure-like events, which induced a 1.3-fold and 1.4-fold increase in CMRO 2 , respectively. 30,54 This underlines the great metabolic demand induced by SD.…”
Section: Cmro 2 Increases 27-fold During Sdmentioning
confidence: 91%
“…Previously, calculations of CMRO 2 relied on p ti O 2 depth profiles acquired by vertical movement of one Clark-style oxygen-electrode in constant steps through acute brain slices (Figure 1(a) and (b)). 30,46,52,54 This method can be used to capture steady-state CMRO 2 , but lacks the temporal resolution necessary for capturing the transient paroxysmal changes in p ti O 2 during SD, which reach a minimum seconds after onset (cf. Figure 2(b)).…”
Section: Three-point Recordings Allow Measurements Of P Ti O 2 Depth ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, only the differentiation of NSCs into neurons was studied, and the differentiation of NSCs into oligodendrocytes, for example, was not assessed. Moreover, while we utilized the sevoflurane concentrations used in our previous study, 22 clinically relevant concentrations, and those commonly used in vitro experiments, 43,44 we did not test the full range of sevoflurane concentrations. Finally, as the association of HDAC9 with CREB in neural stem cells after sevoflurane exposure is a new finding in our study, the mechanism of interaction remains to be further investigated.…”
Section: Of 15mentioning
confidence: 99%
“…Similarly, Xiao et al found PPF exposure in primary rat neurons decreased activation of AMP-activated protein kinase (AMPK), an important cellular signal to promote mitochondrial energy production ( 89 ). Metabolic analysis of isolated rat hippocampal tissue sections indicated that SEV or ISO exposure induces a substantial reduction in metabolic demand proportional to the reduction in neuronal activity, but without any alterations to intrinsic mitochondrial complex activity ( 103 ). These results suggest that reduced bioenergetic signaling and decreased ETC activity may be proportional responses to a GA-induced reduction in neuronal activity.…”
Section: Mitochondrial Targets Of Ga Damagementioning
confidence: 99%